Characterization and Optimization of the Seeding Process of Adipose Stem Cells on the Polycaprolactone Scaffolds. (20th February 2019) - Kurzyk, Agata; Ostrowska, Barbara; Święszkowski, Wojciech; Pojda, Zygmunt
Abstract : The purpose of the current study was to evaluate the usefulness of adipose-derived stem cells (ASCs) for bone injury therapy. Lipoaspirates were collected from the abdomen regions of 17 healthy female donors (mean age 49 ± 6 years) using Coleman technique or Body-jet liposuction. In the present study, the primary objective was the in vitro characteristics of human ASCs. The secondary objective was the optimization of the cell seeding process on 3D-printed scaffolds using polycaprolactone (PCL) or polycaprolactone covered with tricalcium phosphate (PCL + 5% TCP). Biological evaluation of human ASC showed high efficiency of isolation obtaining a satisfying amount of homogeneous cell populations. Results suggest that ASCs can be cultured in vitro for a long time without impairing their proliferative capacity. Growth kinetics shows that the highest number of cells can be achieved in passage 5 and after the 16 th passage; there is a significant decrease of cell numbers and their proliferative potential. The percentage of colony forming units from the adipose stem cells is 8% ± 0.63% (p < 0.05 ). It was observed that the accumulation of calcium phosphate in the cells in vitro, marked with Alizarin Red S, was increased along with the next passage. Analysis of key parameters critically related to the cell seeding process shows that volume of cell suspension and propagation time greatly improve the efficiency of seeding both in PCL and PCL + 5% TCP scaffolds. The cell seeding efficiency did differ significantly between scaffold materials and cell seeding methods (p < 0.001 ). Increased seeding efficiency was observed when using the saturation of cell suspension into scaffolds with additional incubation. Alkaline phosphatase level production in PCL + 5% TCP scaffold was better than in PCL-only scaffold. The study results can be used for the optimization of the seeding process and quantification methods determining the successful implementation of the preclinical model study in the future tissue engineering strategies.